2004
DOI: 10.1007/s10151-004-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ranitidine on healing of normal and transfusion-suppressed experimental anastomoses

Abstract: These data indicate that ranitidine has no influence in anastomotic bursting pressure, but has a lower incidence of septic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
2
1
1
Order By: Relevance
“…Ranitidine has been shown to have no effect on experimental anastomotic strength, but it did result in a lower incidence of septic complications in an animal study. We cannot directly compare the results of this study to our conclusions, as hydroxyproline levels were not reported and the bursting pressure was determined in a different manner 9. In our study, famotidine exerted a significant influence on anastomotic strength and decreased the collagen content of anastomoses in rats.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Ranitidine has been shown to have no effect on experimental anastomotic strength, but it did result in a lower incidence of septic complications in an animal study. We cannot directly compare the results of this study to our conclusions, as hydroxyproline levels were not reported and the bursting pressure was determined in a different manner 9. In our study, famotidine exerted a significant influence on anastomotic strength and decreased the collagen content of anastomoses in rats.…”
Section: Discussioncontrasting
confidence: 57%
“…Histamine H2 receptors accelerate cell proliferation, thereby impacting both lymphocyte and immune system response 8,9…”
Section: Introductionmentioning
confidence: 99%
“…However, the beneficial effect of pharmacotherapy in patient care could not be approved in clinical settings [3,4] . It is clearly shown that a meticulous surgical technique that does not disturb the essential blood supply is a major factor during the first days of intestinal anastomotic healing [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Επίσης, έχει δοκιμασθεί η προστατευτική επίδραση στις αναστομώσεις διαφόρων παραγόντων και ουσιών, όπως ομοιάζων με ινσουλίνη αυξητικός παράγοντας Ι -insulin-like growth factor I (122-126), κόλλα ινικής -fibrin glue (127)(128)(129), ερυθροποιητίνη (130), πρώιμη διεντερική σίτιση (131), simvastatin (132), gentamicin (133), silbenafil (134), iloprost (135,136), pentoxifylline (137), οκτρεοτίδη (138), καθώς και celecoxib (32,139). Εκτός των παραπάνω και άλλες ουσίες έχουν μελετηθεί, όπως azathioprine (140), paclitaxel (141), στεροειδή (142), ρανιτιδίνη (143), mycophenolate mofetic (144), καθώς και η υπερθερμική ενδοπεριτοναϊκή έγχυση χημειοθεραπείας -IPEC (145). Ακόμα, έχει μελετηθεί η επίδραση της μετάγγισης αίματος (146), καθώς και του πνευμοπεριτοναίου (147).…”
unclassified